Research on the performance of a novel SPR sensor based on graded index multimode fiber. Issue 3 (30th November 2018) - Liu, Chunlan; Wei, Yong; Su, Yudong; Liu, Hao; Zhang, Yonghui; Nie, Xiangfei
Abstract : Purpose: This paper aims to propose and demonstrate a novel surface plasmon resonance (SPR)-sensing approach by using the fundamental mode beam based on a graded index multimode fiber (GIF). The proposed SPR sensor has high sensitivity and controllable working dynamic range, which expects to solve the two bottlenecks of fiber SPR sensor, including low sensitivity and the difficulty in multichannel detection. Design/methodology/approach: The low-order mode of the GIF to SPR sense, which keeps the sensitivity advantage of the single-mode fiber SPR sensor, is used. By using this new SPR sensor, the effect of light incident angle and gold film thickness on working dynamic range was studied. According to the study results, the smaller is the incident angle, the larger is the SPR working dynamic range and the longer is the resonance wavelength with a fixed gold film thickness; the larger is the gold film thickness, the longer is the resonance wavelength with a fixed grinding angle. After the parameter optimization, the sensitivity of these two parameter-adjusting methods reach 4, 442 and 3031 nm/RIU. Originality/value: When the grinding angle of the GIF increases, the dynamic range of the resonance wavelength increases and has a redshift, sensitivity increases, and the resonance valley becomes more unobvious with a fixed gold film thickness. Similarly, when gold film thickness increases, the dynamic range of the resonance wavelength increases and has a redshift, sensitivity increases, and the resonance valley becomes more unobvious with a fixed grinding angle. These adjusting performance aforementioned lay the foundation for solving of the fiber-based SPR multichannel detection and increasing of the fiber-based SPR sensor sensitivity, which has a good application value.